CagA-positive Helicobacter pylori may promote and aggravate scrub typhus - Du, Qiuying; Zeng, Houyang; Pang, Xianwu; Cao, Jianyu; Xie, Bo; Long, Chunyi; Liang, Liudan; Deng, Fenglian; Huang, Meijin; Li, Li; Huang, Fengyan; Liu, Xinli; et al. (Frontiers in Microbiology, 2024)
Helicobacter pylori (H. pylori) infection may alter the host's resistance to tsutsugamushi disease pathogens through the Th1 immune response, leading to potential synergistic pathogenic effects. A total of 117 scrub typhus cases at Beihai People's Hospital and affiliated hospitals of Youjiang University for Nationalities and Medical Sciences were studied from January to December 2022, alongside 130 healthy individuals forming the control group. All participants underwent serum H. pylori antibody testing. The prevalence of H. pylori infection was significantly higher among scrub typhus patients (89.7%) compared to healthy individuals (54.6%) (P < 0.05). Moreover, type I H. pylori infection was notably more prevalent in scrub typhus cases (67.5%) compared to healthy individuals (30%) (P < 0.05).factor for scrub typhus (adjusted odds ratio: 2.407, 95% confidence interval: 1.249-4.64, P = 0.009). Among scrub typhus patients with multiple organ damage, the prevalence of type I H. pylori infection was significantly higher (50.6%) than type II H. pylori infection (15.4%) (χ2 = 4.735, P = 0.030). These results highlight a higher incidence of H. pylori infection in scrub typhus patients compared to the healthy population. Additionally, type I H. pylori strain emerged as an independent risk factor for scrub typhus development. Moreover, individuals infected with type I H. pylori are more susceptible to multiple organ damage. These findings suggest a potential role of H. pylori carrying the CagA gene in promoting and exacerbating scrub typhus.